A complex-structure porous silicon nitride ceramic and a rapid preparation method and application thereof
Patent Information
- Application Number
- CN202410691525.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-05-30
AI Technical Summary
[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种复杂结构多孔氮化硅陶瓷及其快速制备方法和应用,以解决现有技术无法实现复杂结构多孔氮化硅陶瓷的高效、低能耗可控制备的技术问题
[0021]本发明采用硅粉和氮化硅粉作为主要原料,添加烧结助剂和粘结剂,通过配制浆料、3D打印成型和燃烧合成快速制备复杂结构多孔氮化硅陶瓷。其中,借助3D打印技术能够制造任意复杂形状的多孔硅/氮化硅生坯,而生坯燃烧时释放的能量不仅保证了其中硅粉的持续氮化,而且能实现其近零能耗高效烧结,无需使用复杂的高温、高压设备,具有工艺简单、重复性好、产量高、成本低、能耗低、周期短等优点。本发明为复杂结构多孔陶瓷的设计制备提供了新思路和新方法,有望拓宽该类材料的应用领域和范围。
Smart Images

Figure CN118666592B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of inorganic non-metallic material preparation, and relates to a complex-structured porous silicon nitride ceramic, its rapid preparation method, and its application. Background Technology
[0002] Complex porous silicon nitride ceramics possess a series of excellent properties, including high specific strength, low coefficient of thermal expansion, good permeability, and high chemical stability, making them one of the most promising catalyst supports for high-temperature gas-phase reactions. However, traditional processes such as adding pore-forming agents, extrusion molding, and gel casting are difficult to obtain complex-structured preforms and suffer from problems such as long preparation cycles, high costs, and difficulty in controlling the macro / microstructure of materials, which severely limit the large-scale engineering application of complex porous silicon nitride ceramics.
[0003] 3D printing technology, based on the principle of discrete-stacking, can fabricate porous ceramic materials with arbitrarily complex geometries. This technology, through complex configuration designs, provides porous silicon nitride with more gas mass and heat transfer pathways, thereby significantly improving catalytic efficiency. Currently, 3D printing technology can be used to prepare various porous ceramic materials with complex structures, such as silicon carbide, alumina, silicon nitride, and hydroxyapatite.
[0004] However, for silicon nitride, due to its high covalent bond energy, low atomic self-diffusion coefficient, and easy decomposition at high temperatures, the field still primarily uses commonly used sintering techniques such as pressure sintering or atmosphere-protected sintering. These techniques all suffer from high temperatures, high energy consumption, and long preparation cycles. There are also reports of silicon nitride preparation using 3D printing technology, such as the invention patent CN107586136A, "A Method for 3D Printing Silicon Nitride Ceramics," which uses Si3N4 powder, sintering aids, and photocurable resin as raw materials. Si3N4 ceramics are obtained through 3D printing, debinding, and high-temperature pressure sintering. However, this method involves complex preparation processes, high-pressure and high-energy-consumption sintering, and poor controllability of the product's pore structure. Therefore, how to achieve efficient, low-energy-consumption, and controllable preparation of complex porous silicon nitride ceramics is a pressing problem to be solved. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a complex-structured porous silicon nitride ceramic and its rapid preparation method and application, so as to solve the technical problem that the prior art cannot achieve efficient, low-energy-consumption, and controllable preparation of complex-structured porous silicon nitride ceramics.
[0006] To achieve the above objectives, the present invention employs the following technical solution:
[0007] This invention discloses a rapid preparation method for complex-structured porous silicon nitride ceramics, comprising the following steps:
[0008] 1) Mix silicon powder, silicon nitride powder, sintering aid, binder and solvent evenly to prepare a slurry;
[0009] 2) Design and build a three-dimensional model, and 3D print the slurry to obtain a complex structure silicon / silicon nitride green blank;
[0010] 3) Dry the complex structure silicon / silicon nitride green body, then use silicon nitride powder as a pre-embedded powder, and allow the complex structure silicon / silicon nitride green body to spontaneously combust in a nitrogen atmosphere. After the combustion reaction is completed, a complex structure porous silicon nitride ceramic is obtained.
[0011] Preferably, in step 1), the mass ratio of silicon powder to silicon nitride powder is (45-65):(35-55); the sintering aid is alumina and yttrium oxide in a molar ratio of 5:3, and the amount of sintering aid added is 3%-8% of the total mass of silicon powder and silicon nitride powder; the binder is polyvinyl alcohol, and the amount of binder added is 2% of the total mass of silicon powder and silicon nitride powder; the solvent is water; and the solid content of the obtained slurry is 58%-73%.
[0012] Preferably, in step 2), a 3D model is designed and built using Cura slicing software. Other slicing software options include PrusaSlicer, Bambu Studio, and Lychee. The slurry is then molded using a direct-write 3D printer. Other 3D printing equipment can also be used; direct-write equipment is simple and has low operating costs.
[0013] More preferably, the infill density of the 3D model is 40%–55%, the nozzle diameter of the direct-write 3D printer is 0.7–1.2 mm, and the printing speed is 45–70 mm / s. Under these parameters, a structurally stable blank can be printed.
[0014] Preferably, in step 3), the drying process is to dry at 40°C for 24 hours.
[0015] Preferably, in step 3), the vacuum and nitrogen atmosphere are achieved by evacuating the reaction chamber to a pressure less than 10 Pa, followed by filling it with nitrogen gas of 99.999% purity, with a nitrogen pressure of 2–7 MPa within the reaction chamber. The printed green body contains silicon; after localized ignition of the green body, the silicon reacts with nitrogen gas under high-pressure nitrogen to form silicon nitride. The heat released by the reaction simultaneously sintersulates the green body, eliminating the need for continuous external heating.
[0016] Preferably, in step 3), a current of 50A is passed through both ends of the graphite paper strip at the bottom of the complex structure silicon / silicon nitride green blank for 10s to cause it to spontaneously combust.
[0017] The present invention also discloses a complex-structured porous silicon nitride ceramic prepared by the above-mentioned rapid preparation method. The complex-structured porous silicon nitride ceramic exhibits a three-dimensional mesh structure, with a printing layer thickness of 0.37-0.49 mm, a filament diameter of 0.59-1.08 mm, a filament spacing of 0.22-1.09 mm, a filament porosity of 42%-63%, and a compressive strength of 4.3-45.1 MPa.
[0018] The present invention also discloses the application of the above-mentioned complex porous silicon nitride ceramics in the preparation of high-temperature catalyst supports.
[0019] The present invention also discloses the application of the above-mentioned complex-structured porous silicon nitride ceramics in the preparation of high-temperature filtration and separation materials.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] This invention uses silicon powder and silicon nitride powder as the main raw materials, adding sintering aids and binders, to rapidly prepare complex-structured porous silicon nitride ceramics through slurry preparation, 3D printing molding, and combustion synthesis. The 3D printing technology enables the fabrication of porous silicon / silicon nitride green bodies of arbitrarily complex shapes. The energy released during the combustion of the green body not only ensures the continuous nitridation of the silicon powder but also achieves near-zero energy consumption and efficient sintering, eliminating the need for complex high-temperature, high-pressure equipment. This invention offers advantages such as simple process, good repeatability, high yield, low cost, low energy consumption, and short cycle time. This invention provides new ideas and methods for the design and fabrication of complex-structured porous ceramics, and is expected to broaden the application fields and scope of this type of material.
[0022] The complex porous silicon nitride ceramic prepared by the method of this invention exhibits a three-dimensional mesh structure. It has a complex structure, uniform and controllable pore structure, and many mass and heat transfer paths inside. It can be used as a high-temperature catalyst support or filtration and separation material, and has good application prospects in energy, chemical and other fields. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the 3D printing process;
[0024] Wherein: 1 is the nozzle; 2 is the injection cylinder; 3 is the complex structure green body.
[0025] Figure 2 The image shows the XRD pattern of the complex-structured porous silicon nitride ceramic prepared by this invention.
[0026] Figure 3 This is a macroscopic photograph of the complex-structured porous silicon nitride ceramic obtained by this invention;
[0027] Figure 4These are microscopic SEM images of the complex-structured porous silicon nitride ceramics prepared by this invention; wherein, (a) is a low-magnification SEM image; and (b) is a magnified SEM image of the filament. Detailed Implementation
[0028] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0029] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0030] The present invention will now be described in further detail with reference to the accompanying drawings:
[0031] Note: The Cura slicing software used in this embodiment of the invention is an open-source software designed specifically for 3D printing, developed by Ultimaker. It supports multiple file formats, provides rich settings options and special features, and can help users slice 3D models and generate high-quality G-code files. Of course, other alternative software can also be selected.
[0032] Example 1
[0033] First, using deionized water as a solvent, 45g of silicon powder, 55g of silicon nitride powder, 5g of sintering aid (alumina and yttrium oxide in a molar ratio of 5:3), and 2g of polyvinyl alcohol were mixed by ball milling to prepare a homogeneous slurry with good rheological properties and a solid content of 62wt%. Then, a three-dimensional model was created using Cura slicing software, and the slurry was molded using a direct-write 3D printer to obtain a complex-structured silicon / silicon nitride green body. Figure 1The model had an infill density of 46%, a nozzle diameter of 1.1 mm, and a printing speed of 45 mm / s. Subsequently, the complex-structured green body was placed in a 40°C electric heating drying oven and dried for 24 hours. The dried green body was then placed in a combustion synthesis apparatus and subjected to powder embedding treatment. Finally, the reaction chamber was evacuated to a pressure less than 10 Pa, and then high-purity (99.999% purity) nitrogen was introduced to a pressure of 7 MPa. A 50 A current was passed through both ends of the graphite paper strip at the bottom of the green body for 10 seconds, causing it to spontaneously combust. After the furnace temperature cooled to room temperature, the extracted block was the complex-structured porous silicon nitride ceramic.
[0034] The phase composition of the material was characterized using X-ray diffraction; the porosity of the filaments was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy, and the thickness of the printed layer, the diameter of the filaments, and the spacing between the filaments were analyzed using Nanomeasure software; and the compressive strength of the material was tested using a universal testing machine. Figure 2 The XRD pattern of the complex porous silicon nitride ceramic obtained is shown. All peaks correspond to the β-Si3N4 phase, and no peaks of any impurity phases are observed. Figure 3 These are macroscopic photographs of the complex porous silicon nitride ceramics that were fabricated. Figure 4 This is a microscopic morphology image of the fabricated complex-structured porous silicon nitride ceramic. It can be seen that the complex-structured porous silicon nitride ceramic prepared in this embodiment exhibits a three-dimensional mesh structure, with a printing layer thickness of 0.49 mm, a filament diameter of 0.96 mm, and a filament spacing of 0.61 mm. Test results show that the filament porosity is 63% and the compressive strength is 4.3 MPa.
[0035] Example 2
[0036] First, using deionized water as a solvent, 57g of silicon powder, 43g of silicon nitride powder, 3g of sintering aid (alumina and yttrium oxide in a molar ratio of 5:3), and 2g of polyvinyl alcohol were mixed by ball milling to prepare a homogeneous slurry with good rheological properties and a solid content of 60wt%. Then, a 3D model was created using Cura slicing software, and the slurry was shaped using a direct-write 3D printer to obtain a complex-structured silicon / silicon nitride green body. The model had an infill density of 52%, a nozzle diameter of 0.9mm, and a printing speed of 60mm / s. Subsequently, the complex-structured green body was placed in a 40℃ electric heating oven and dried for 24 hours. The dried green body was then placed in a combustion synthesis device for powder embedding. Finally, the reaction chamber was evacuated to a pressure less than 10Pa, and then high-purity nitrogen was introduced to a pressure of 5MPa. A 50A current was passed through both ends of the graphite paper strip at the bottom of the green body for 10s, causing it to spontaneously combust. After the temperature inside the furnace cools down to room temperature, the block removed is a complex porous silicon nitride ceramic.
[0037] The porosity of the filaments was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy, and the thickness of the printed layer, the diameter of the filaments, and the spacing between the filaments were analyzed using Nanomeasure software; the compressive strength of the material was tested using a universal testing machine. The results show that the complex porous silicon nitride ceramic prepared in this embodiment exhibits a three-dimensional mesh structure, with a printed layer thickness of 0.39 mm, a filament diameter of 0.79 mm, a filament spacing of 0.94 mm, a filament porosity of 52%, and a compressive strength of 15.8 MPa.
[0038] Example 3
[0039] First, using deionized water as a solvent, 49g of silicon powder, 51g of silicon nitride powder, 6g of sintering aid (alumina and yttrium oxide in a molar ratio of 5:3), and 2g of polyvinyl alcohol were mixed by ball milling to prepare a homogeneous slurry with good rheological properties and a solid content of 63wt%. Then, a 3D model was created using Cura slicing software, and the slurry was shaped using a direct-write 3D printer to obtain a complex-structured silicon / silicon nitride green body. The model had an infill density of 40%, a nozzle diameter of 1.2mm, and a printing speed of 50mm / s. Subsequently, the complex-structured green body was placed in a 40℃ electric heating oven and dried for 24 hours. The dried green body was then placed in a combustion synthesis device for powder embedding. Finally, the reaction chamber was evacuated to a pressure less than 10Pa, and then high-purity nitrogen was introduced to a pressure of 6MPa. A 50A current was passed through both ends of the graphite paper strip at the bottom of the green body for 10s, causing it to spontaneously combust. After the temperature inside the furnace cools down to room temperature, the block removed is a complex porous silicon nitride ceramic.
[0040] The porosity of the filaments was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy, and the thickness of the printed layer, the diameter of the filaments, and the spacing between the filaments were analyzed using Nanomeasure software; the compressive strength of the material was tested using a universal testing machine. The results show that the complex porous silicon nitride ceramic prepared in this embodiment exhibits a three-dimensional mesh structure, with a printed layer thickness of 0.45 mm, a filament diameter of 1.08 mm, a filament spacing of 1.09 mm, a filament porosity of 60%, and a compressive strength of 6.7 MPa.
[0041] Example 4
[0042] First, using deionized water as a solvent, 53g of silicon powder, 47g of silicon nitride powder, 4g of sintering aid (alumina and yttrium oxide in a molar ratio of 5:3), and 2g of polyvinyl alcohol were mixed by ball milling to prepare a homogeneous slurry with good rheological properties and a solid content of 64wt%. Then, a 3D model was created using Cura slicing software, and the slurry was shaped using a direct-write 3D printer to obtain a complex-structured silicon / silicon nitride green body. The model had an infill density of 49%, a nozzle diameter of 1.0mm, and a printing speed of 65mm / s. Subsequently, the complex-structured green body was placed in a 40℃ electric heating oven and dried for 24 hours. The dried green body was then placed in a combustion synthesis device for powder embedding. Finally, the reaction chamber was evacuated to a pressure less than 10Pa, and then filled with high-purity nitrogen to a pressure of 4MPa. A 50A current was passed through both ends of the graphite paper strip at the bottom of the green body for 10s, causing it to spontaneously combust. After the temperature inside the furnace cools down to room temperature, the block removed is a complex porous silicon nitride ceramic.
[0043] The porosity of the filaments was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy, and the thickness of the printed layer, the diameter of the filaments, and the spacing between the filaments were analyzed using Nanomeasure software; the compressive strength of the material was tested using a universal testing machine. The results show that the complex porous silicon nitride ceramic prepared in this embodiment exhibits a three-dimensional mesh structure, with a printed layer thickness of 0.42 mm, a filament diameter of 0.92 mm, a filament spacing of 0.79 mm, a filament porosity of 56%, and a compressive strength of 10.2 MPa.
[0044] Example 5
[0045] First, using deionized water as a solvent, 65g of silicon powder, 35g of silicon nitride powder, 8g of sintering aid (alumina and yttrium oxide in a molar ratio of 5:3), and 2g of polyvinyl alcohol were mixed by ball milling to prepare a homogeneous slurry with good rheological properties and a solid content of 61wt%. Then, a 3D model was created using Cura slicing software, and the slurry was shaped using a direct-write 3D printer to obtain a complex-structured silicon / silicon nitride green body. The model had an infill density of 43%, a nozzle diameter of 0.7mm, and a printing speed of 55mm / s. Subsequently, the complex-structured green body was placed in a 40℃ electric heating oven and dried for 24 hours. The dried green body was then placed in a combustion synthesis device for powder embedding. Finally, the reaction chamber was evacuated to a pressure less than 10Pa, and then high-purity nitrogen was introduced to a pressure of 2MPa. A 50A current was passed through both ends of the graphite paper strip at the bottom of the green body for 10s, causing it to spontaneously combust. After the temperature inside the furnace cools down to room temperature, the block removed is a complex porous silicon nitride ceramic.
[0046] The porosity of the filaments was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy, and the thickness of the printed layer, the diameter of the filaments, and the spacing between the filaments were analyzed using Nanomeasure software; the compressive strength of the material was tested using a universal testing machine. The results show that the complex porous silicon nitride ceramic prepared in this embodiment exhibits a three-dimensional mesh structure, with a printed layer thickness of 0.33 mm, a filament diameter of 0.59 mm, a filament spacing of 0.41 mm, a filament porosity of 42%, and a compressive strength of 45.1 MPa.
[0047] Example 6
[0048] First, using deionized water as a solvent, 61g of silicon powder, 39g of silicon nitride powder, 7g of sintering aid (alumina and yttrium oxide in a molar ratio of 5:3), and 2g of polyvinyl alcohol were mixed by ball milling to prepare a homogeneous slurry with good rheological properties and a solid content of 65wt%. Then, a 3D model was created using Cura slicing software, and the slurry was shaped using a direct-write 3D printer to obtain a complex-structured silicon / silicon nitride green body. The model had an infill density of 55%, a nozzle diameter of 0.8mm, and a printing speed of 70mm / s. Subsequently, the complex-structured green body was placed in a 40℃ electric heating oven and dried for 24 hours. The dried green body was then placed in a combustion synthesis device for powder embedding. Finally, the reaction chamber was evacuated to a pressure less than 10Pa, and then high-purity nitrogen was introduced to a pressure of 3MPa. A 50A current was passed through both ends of the graphite paper strip at the bottom of the green body for 10s, causing it to spontaneously combust. After the temperature inside the furnace cools down to room temperature, the block removed is a complex porous silicon nitride ceramic.
[0049] The porosity of the filaments was tested using the Archimedes displacement method; the microstructure of the material was characterized using field emission scanning electron microscopy, and the thickness of the printed layer, the diameter of the filaments, and the spacing between the filaments were analyzed using Nanomeasure software; the compressive strength of the material was tested using a universal testing machine. The results show that the complex porous silicon nitride ceramic prepared in this embodiment exhibits a three-dimensional mesh structure, with a printed layer thickness of 0.37 mm, a filament diameter of 0.71 mm, a filament spacing of 0.22 mm, a filament porosity of 48%, and a compressive strength of 25.6 MPa.
[0050] In summary, this invention is the first to utilize a combination of 3D printing and combustion synthesis to prepare complex-structured porous silicon nitride ceramics. This method eliminates the need for complex high-temperature, high-pressure equipment, overcoming the difficulty of forming complex green bodies using traditional processes and avoiding the use of high-pressure, high-energy-consuming gas pressure sintering equipment. Therefore, it offers advantages such as simple process, good repeatability, high yield, low cost, low energy consumption, and short cycle time. The complex-structured porous silicon nitride ceramics prepared by this invention have complex structures, uniform and controllable pore structures, and numerous internal mass and heat transfer pathways. They can be used as high-temperature catalyst supports or filtration and separation materials, showing promising application prospects in energy, chemical, and other fields.
[0051] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A rapid preparation method for complex-structured porous silicon nitride ceramics, characterized in that, Includes the following steps: 1) Silicon powder, silicon nitride powder, sintering aid, binder, and solvent are mixed evenly to prepare a slurry; the mass ratio of silicon powder to silicon nitride powder is (45~65):(35~55); the sintering aid is alumina and yttrium oxide with a molar ratio of 5:3, and the amount of sintering aid added is 3%~8% of the total mass of silicon powder and silicon nitride powder; the binder is polyvinyl alcohol, and the amount of binder added is 2% of the total mass of silicon powder and silicon nitride powder; the solvent is water; the solid content of the prepared slurry is 58%~73%. 2) Design and build a three-dimensional model, and use a direct-write 3D printer to form the slurry to obtain a complex structure silicon / silicon nitride green body; 3) Dry the complex structure silicon / silicon nitride green body, then use silicon nitride powder as a embedding powder, and under a nitrogen atmosphere, pass a current of 50A for 10s through both ends of the graphite paper tape at the bottom of the complex structure silicon / silicon nitride green body to make the complex structure silicon / silicon nitride green body spontaneously combust. After the combustion reaction is completed, a complex structure porous silicon nitride ceramic is obtained.
2. The rapid preparation method for complex-structured porous silicon nitride ceramics according to claim 1, characterized in that, In step 2), a 3D model is designed and built using the Cura slicing software.
3. The rapid preparation method of complex-structured porous silicon nitride ceramics according to claim 2, characterized in that, The infill density of the 3D model is 40%~55%, the nozzle diameter of the direct-write 3D printer is 0.7~1.2 mm, and the printing speed is 45~70 mm / s.
4. The rapid preparation method for complex-structured porous silicon nitride ceramics according to claim 1, characterized in that, In step 3), the drying process involves drying at 40°C for 24 hours.
5. The rapid preparation method of complex-structured porous silicon nitride ceramics according to claim 1, characterized in that, In step 3), the vacuum and nitrogen atmosphere are achieved by evacuating the reaction chamber to a pressure of less than 10 Pa and then filling it with nitrogen gas of 99.999% purity. The nitrogen pressure in the reaction chamber is 2~7 MPa.
6. A complex-structured porous silicon nitride ceramic prepared by the rapid preparation method according to any one of claims 1 to 5, characterized in that, This complex porous silicon nitride ceramic exhibits a three-dimensional mesh structure with a printed layer thickness of 0.37~0.49mm, a filament diameter of 0.59~1.08mm, a filament spacing of 0.22~1.09mm, a filament porosity of 42%~63%, and a compressive strength of 4.3~45.1MPa.
7. The application of the complex-structured porous silicon nitride ceramic of claim 6 in the preparation of high-temperature catalyst supports.
8. The application of the complex-structured porous silicon nitride ceramic of claim 6 in the preparation of high-temperature filtration and separation materials.
Citation Information
Patent Citations
Method for preparing silicon nitride ceramics through 3D printing
CN107586136A
Porous Si3N4 (silicon nitride) ceramic based on additive manufacturing technology as well as preparation method and application thereof
CN107353036A
Preparation method of porous silicon nitride ceramic with oriented pore structure
CN111410540A